THE INFLUENCE OF CONTEXT CLUES STRATEGY ON STUDENTSâ€™ READING ACHIEVEMENT - Yus Vernandes (Universitas PGRI Palembang, 2019)
The main problem of this study was â€œIs there any significant influence of context clues strategy on student reading narrative text achievement of the tenth grade students of state Senior High School 2 of Palembang?â€. Therefore, objective of this study was to find out whether or not there is significant influence of context clues strategy to their reading ability of the tenth grade students of state Senior High School 2 of Palembang. The population of this study was 185 students consisting of five classes. The writer took the sample from the population through purposive non random sampling with the total 37 students. In this study, the writer used pre-experimental method, the data were collected through the written test and where analyzed by using the matched t-test. Based on the findings, the studentsâ€™ average score in the pre-test was 55.74 the highest score in the pre-test was 82.5 achieved by one student and the lowest score in the pre-test was 2.5 achieved by one student. The average score in the post-test was 70.60, the highest score was 87.5 achieved by one student, and the lowest score was 57.5 obtained by three students. To compare the studentsâ€™ score in pre-test and the posttest, matched t-test was used, and it was found that t-obtained (6.016) was higher than critical value t-table (1.684). It means that Ho was rejected and Ha was accepted. In means that there was a significant influence of context clues strategy on student reading narrative text achievement of the tenth grade students of state Senior High School 2 of Palembang